Estimating travel time to urban areas of different population sizes - Nelson, A.; Weiss, D. J.; van Etten, J.; Cattaneo, A.; McMenomy, T. S.; Koo, Jawoo (European Commission, 2021)
Access to the resources, services and opportunities that are concentrated in urban areas is an important indicator for development. Urban areas and the transport networks that connect them together and to their surrounding rural areas are essential infrastructure. This infrastructure provides the means for people and products to travel from A to B. It enables social and economic interactions and the delivery of basic services such as education and healthcare. People with good access generally have greater opportunity for social and economic development, reduced costs and greater levels of interaction, whereas those with poor access generally face higher costs, fewer opportunities and poorer health and education outcomes.